If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8 + u)(4u + 1) = 0 Reorder the terms: (8 + u)(1 + 4u) = 0 Multiply (8 + u) * (1 + 4u) (8(1 + 4u) + u(1 + 4u)) = 0 ((1 * 8 + 4u * 8) + u(1 + 4u)) = 0 ((8 + 32u) + u(1 + 4u)) = 0 (8 + 32u + (1 * u + 4u * u)) = 0 (8 + 32u + (1u + 4u2)) = 0 Combine like terms: 32u + 1u = 33u (8 + 33u + 4u2) = 0 Solving 8 + 33u + 4u2 = 0 Solving for variable 'u'. Factor a trinomial. (8 + u)(1 + 4u) = 0Subproblem 1
Set the factor '(8 + u)' equal to zero and attempt to solve: Simplifying 8 + u = 0 Solving 8 + u = 0 Move all terms containing u to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + u = 0 + -8 Combine like terms: 8 + -8 = 0 0 + u = 0 + -8 u = 0 + -8 Combine like terms: 0 + -8 = -8 u = -8 Simplifying u = -8Subproblem 2
Set the factor '(1 + 4u)' equal to zero and attempt to solve: Simplifying 1 + 4u = 0 Solving 1 + 4u = 0 Move all terms containing u to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 4u = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 4u = 0 + -1 4u = 0 + -1 Combine like terms: 0 + -1 = -1 4u = -1 Divide each side by '4'. u = -0.25 Simplifying u = -0.25Solution
u = {-8, -0.25}
| x^2+12ax+35a^2=0 | | X^2+6x+43=0 | | 68=6x+6x+8 | | 9x-8=2x+34 | | -2z^2+5z+3=0 | | 3(y-5)+1=2y+34-2y | | -5x-3y-5x-8y= | | -43=-61+x | | 4ay/3d | | (x+y)=80 | | 2x^2-8x-100=20 | | X/27/2 | | x^3-8x^2-33x+26=0 | | 5z-6+6=-36+z | | 9a+2a-8a-3b= | | 29b-93=7 | | 5(2x-10)/2 | | 3x+7=9x+5 | | 4v^2+25v+21=0 | | 16a+8b+1=0 | | 12-b=0 | | (-7b-2c)+(6b-3c-1)= | | X+3x+(x+7)=32 | | 8a(-3a)= | | 50=1.75x | | -((-3)+3)= | | 5x+8=9x-8 | | 16a+8a+1=0 | | b(b-3)=28 | | 0=-16x^2+1400 | | 12=780x | | 6x-46=4x+76 |